Cloning of variable fragments of tumor immunoglobulin, assembling and expressing of human SCFV protein in E. coli for anti-idiotype vaccination - Meleshko, A.N.; Vashkevich, K.P.; Fomina, E.G.; Scheslenok, E.P.; Schkolina, T.V.; Sergeev, G.V. (Experimental Oncology, 2013)
Aim: Idiotype, the unique part of immunoglobulin molecule expressed on the surface of B-cells, represents a specific antigen for vaccination against lymphoma. We have developed a rapid method for immunoglobulin variable fragments cloning, assembling and expression of recombinant idiotype protein in Escherichia coli. Methods: PCR with specially designed panel of primers was used for direct amplification of variable regions of tumor immunoglobulin. Overlapping extension PCR, restriction and ligation was applied for assembling and cloning of vaccine construction. Idiotype protein was purified by metal-chelate chromatography. Results: Methods of idiotype cloning from lymphoma cells and production of recombinant protein were developed and optimized. Several samples of idiotypic proteins originating from B-cell lines and lymphoma patients were produced. Conclusion: The proposed method of vaccine production is relatively cheap, not very laborious and requires as long as 6–7 week to perform. The expressed protein was soluble, did not accumulate in inclusion bodies and harvested at sufficient for vaccination quantity and concentration.